Model pergerakan udara pada lingkungan termal dalam bangunan dengan elemen air dan lansekap sebagai pengubah iklim mikro di iklim tropis panas dan lembab - Hamdy, Muhammad Awaluddin; Hamzah, Baharuddin; Wikantari, Ria; Mulyadi, Rosady (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Thermal comfort in buildings is determined by several aspects of the climate, such as external and internal wind speeds. Therefore, this research aims to analyze the effect of water elements and vegetation as microclimate modifiers in buildings, to obtain thermal comfort through air velocity and flow analysis. In this context, the field analysis emphasized microclimate parameters. Two cases were also encompassed, namely the interior space of a residential building and a shopping center. By using field measurements with quantitative methods, data were obtained through the analysis of the PMV (thermal comfort index Predicted Mean Vote), PPD (Predicted Percentage of Dissatisfied), and TSV (Thermal Sensation Vote). This experiment was conducted to determine the influential levels of the building water and vegetation on comfort and the thermal environment. Data analysis was also processed using a statistical approach, with airflow being simulated through CFD (Computational Fluid Dynamics) method. The results showed that the air movement occurring in the building to the comfort and thermal environment, through architectural elements, reduced the temperature and humidity in the room. This was due to the heat radiation outside the building, leading to an impact on the effective air temperature for the thermal sensation of visitors. In this case, the movement of air in the building with the placement of architectural elements, such as water, vegetation, and good ventilation, was important for various activities. These activities included the following, (1) providing positive value, (2) improving the quality of the indoor environment, (3) maintaining the stability of the thermal environment at the building scale, and (4) achieving a comfortable thermal sensation.